TEORI KOGNITIF DALAM AL-QURAN - Rohman, Minanur (LPPI Universitas Al-Qolam Malang, 2014)
Many experts have proposed theory of learnig mathematics, namely, â€œhow a mathematical concept can exist in the studentsâ€™ minds.â€ Pieget stressed that abstraction is an important thing when learning math concept. As for David Tall, abstraction capability is also required in addition to the awareness that there are symbol in mathematics. How the Qurâ€™an describes the idea of learning mathematics?Keywords: Teori kognitif, abstraction, conception, teori kognitif dalam Al-Qurâ€™an.